THE FACTORS RELATED TO H. PYLORI INFECTION RESISTANCE AFTER ERADICATION OR ITS RECURRENCE IN SULAIMANI CITY - Ahmad, Hazhan Nawzad; Abdulkareem, Makwan Mohammed; Alshekhani, Muhamad Abdularahman Muhamad (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Helicobacter pylori (H. pylori) infection can lead to peptic ulcers, chronic gastritis, lymphoma and gastric cancer. This study aimed to assess the factors related to H. pylori resistance after eradication and its recurrence after 6 months. 574 patients tested for H. pylori and those who positive has been assessed for recurrence after 6 months or resistance to treatment and factors related to recurrence in correlation with demographic data. 51% of men and 49% of women were still testing positive for H. pylori after receiving treatment.   The majority of patients who tested positive again for H. pylori were taking clarithromycin-based triple therapy, with only a small percentage being treated with levofloxacin, rate of resistance and recurrence were 23.54% and 8.7%, respectively. Most common symptoms after recurrence were epigastric pain and nausea (62.96%) and dyspepsia (55.55%). The highest rate of recurrence is related to O+ blood group, which is 47.82%. Recurrence rate after H. pylori eradication by standard therapy (clarithromycin triple treatment) or levofloxacin-based therapy is 8.7%. Poor sanitation, low income, and treatments regimens are independent risk factors for recurrence of H. pylori. Reducing the frequency of eating outdoors and treating family members may reduce H. pylori infection recurrence.